Fascin Expression in Ameloblastoma, Odontogenic Keratocyst and Dentigerous Cyst - Sedigheh RAHROTABAN; Nariman NIKPARTO; Parham YOUSEFIZADEH; Mohammad Javad KHARAZIFARD; Samira DERAKHSHAN (Türk Patoloji Dergisi, 2018)

(untitled)
Objective: The purpose of this study was to assess and compare fascin expression in 4 lesions which differ in aggressiveness: odontogenic keratocyst, dentigerous cyst and two types of ameloblastoma (solid and unicystic), and to find out whether fascin expression is associated with aggressiveness of these lesions or not.